Social exchange and psychological ownership as complementary pathways from psychological contract fulfillment to organizational citizenship behaviors. Issue 6 (27th October 2020) - Gardner, Donald G.; Pierce, Jon L.; Peng, He
Abstract : Purpose: Social comparison and job-based psychological ownership (JPO) are compared and contrasted as explanations for relationships between organization relational psychological contract fulfillment (ORPCF) and organizational citizenship behaviors (OCBs). Design/methodology/approach: Survey data were collected from 241 employees and 82 of their managers at an information services company. Data were analyzed using structural equation modeling to test for hypothesized and exploratory indirect relationships. Findings: Consistent results were found for sequential mediation from ORPCF to employee investment of the self into the job, to JPO, to supervisor-rated helping and voice OCBs. Employees' perception of their relational psychological contract fulfillment (social exchange) did not simultaneously mediate the relationships between ORPCF and employees' OCBs. Research limitations/implications: Psychological ownership presents a complement to social exchange to explain effects of relational psychological contract fulfillment on employee outcomes. Because of the cross-sectional nature of the data conclusions about causality are quite limited. Practical implications: Organizations and managers should emphasize that fulfillment of relational psychological contract obligations represent a significant investment in employees, who reciprocate by investing themselves into their work. This in turn bolsters JPO and its positive employee outcomes. Originality/value: This is the first study to directly compare social exchange and psychological ownership explanations for effects of psychological contract fulfillment on employees.